Punishment for Crime- Influence on Personality - Rice, Delbert (Silliman Journal, 2024)
The author summarizes five concepts of punishment for crime—isolation, retribution, deterrence, reformation and restoration. He shows that restoration is the most effective, and gives examples taken from the practice of the Kalahans, a cultural minority in northern Luzon.